AKIBAT HUKUM TERHADAP OBYEK JAMINAN FIDUSIA YANG SUDAH DIALIHKAN SEBELUM JAMINAN FIDUSIA DIDAFTARKAN - Surya Eka Prayuda, Putu Gede; -, Adiwati; Mudana, I Nyoman (Kertha Wicara : Journal Ilmu Hukum; Vol. 02, No. 02, April 2013)
Birth of fiduciary guarantee is the same date as the date of registration fiduciary guarantee. Before fiduciary guarantee registered, the position of fiduciary recipients is very weak. So, to acquire the legal certainty, the fiduciary guarantee must be registered. Fiduciary recipient who have registered will acquire benefit as preferent creditors, while fiduciary recipient who have not registered serve as concurrent creditors. And fiduciary guarantee also has the power executorial, creditors as fiduciary recipient have the right to execute the guarantee object if the debitor is default
Keywords: Legal Consequence, Object Fiduciary Guarantee, Diversion, Fiduciary Guarantee Registration.